Blood‐based bioenergetic profiling reveals differences in mitochondrial function associated with cognitive performance and Alzheimer's disease. Issue 4 (23rd July 2022) - Mahapatra, Gargi; Gao, Zhengrong; Bateman, James R.; Lockhart, Samuel Neal; Bergstrom, Jaclyn; DeWitt, Amber Renee; Piloso, Jemima Elizabeth; Kramer, Philip Adam; Gonzalez‐Armenta, Jenny L.; Amick, Kimberly Allison; Casanova, Ramon; Craft, Suzanne; et al.
Abstract: Introduction: Despite evidence for systemic mitochondrial dysfunction early in Alzheimer's disease (AD) pathogenesis, reliable approaches monitoring these key bioenergetic alterations are lacking. We used peripheral blood mononuclear cells (PBMCs) and platelets as reporters of mitochondrial function in the context of cognitive impairment and AD. Methods: Mitochondrial function was analyzed using complementary respirometric approaches in intact and permeabilized cells from older adults with normal cognition, mild cognitive impairment (MCI), and dementia due to probable AD. Clinical outcomes included measures of cognitive function and brain morphology. Results: PBMC and platelet bioenergetic parameters were lowest in dementia participants. MCI platelets exhibited higher maximal respiration than normocognitives. PBMC and platelet respiration positively associated with cognitive ability and hippocampal volume, and negatively associated with white matter hyperintensities. Discussion: Our findings indicate blood‐based bioenergetic profiling can be used as a minimally invasive approach for measuring systemic bioenergetic differences associated with dementia, and may be used to monitor bioenergetic changes associated with AD risk and progression. Highlights: Peripheral cell bioenergetic alterations accompanied cognitive decline in older adults with mild cognitive impairment (MCI) and Alzheimer's disease (AD) and related dementia (DEM). Peripheral blood mononuclear cells (PBMC) and platelet glucose‐mediated respiration decreased in participants with dementia compared to normocognitive controls (NC). PBMC fatty‐acid oxidation (FAO)‐mediated respiration progressively declined in MCI and AD compared to NC participants, while platelet FAO‐mediated respiration exhibited an inverse‐Warburg effect in MCI compared to NC participants. Positive associations were observed between bioenergetics and Modified Preclinical Alzheimer's Cognitive Composite, and bioenergetics and hippocampal volume %, while a negative association was observed between bioenergetics and white matter hyperintensities. Systemic mitochondrial dysfunction is associated with cognitive decline.